Solute Front Shear and Coalescence Control Concentration Gradient Dynamics in Porous Micromodel. Issue 5 (2nd March 2023) - Borgman, Oshri; Turuban, Régis; Géraud, Baudouin; Le Borgne, Tanguy; Méheust, Yves
Abstract: In subsurface environments, incomplete mixing at the pore scale limits reaction rates, rendering their prediction by Darcy‐scale models challenging. Such pore scale concentration gradients are enhanced by the deformation of solute fronts and decay under the action of molecular diffusion and solute filament merging. It is currently unclear how these processes govern concentration gradient dynamics under different flow rates. We measure experimentally pore scale concentrations in solute fronts transported in a two‐dimensional porous micromodel over an extensive range of flow rates. We demonstrate that pore‐scale shear flow increases concentration gradients up to a time predicted by the lamellar mixing theory in shear flow. However, the flow rate‐dependency of the mean concentration gradient at this so‐called mixing time is weaker than predicted theoretically, a discrepancy which we explain quantitatively by accounting for lamellae aggregation. These findings shed new light on the pore‐scale mechanisms driving mixing dynamics in porous media. Plain Language Summary: Solute mixing is the process that homogenizes chemical species' concentrations over space in time. Solute mixing rates are crucial to chemical reactions associated with environmental flow phenomena. Classical flow and transport models use solute concentration values averaged over length scales of a few millimeters and higher. But concentrations can show substantial variations at single pores' sub‐millimetric length scales, which impact large‐scale reaction rates. Besides, the heterogeneous porous structure of subsurface natural materials causes flow velocity variations between solid grains, which impact spatial variations of concentration within solute plumes. We present solute transport experiments in a flow cell mimicking the geometry of natural porous media. The transparent flow cell allows direct measuring of the concentration of a fluorescent dye injected at various flow rates to infer their impact on concentration variations. The recently introduced lamellar mixing theory describes the overall time dynamics of concentration variations well. However, the maximum mixing rates differ from theoretical predictions due to an additional mechanism currently not considered in the theory: the aggregation of solute lamellae. This work establishes the full relevance of the lamellar mixing theory to porous media flow when accounting for lamellae aggregation. Key Points: We analyze experimental pore‐scale concentrations ( c ) and gradients over an extensive range of Pe The time of maximum c ‐gradient is predicted by the lamella mixing theory assuming simple shear flow The maximum c ‐gradient values are limited by aggregation between solute filaments